Democratic Party Fundraiser with Congressman Tony Coelho at Watkins' Backyard - Watkins, Howard::::::::: (1983)
Margaret Johnson (wife of Willard "Bill" Johnson), Jim Kratzer, Lois Ehrenberg, Tony Coelho, Darci Reid Noxon